The IMF's Principal Tasks - Guidelines for a Reform Programme - Detlef Radke (Deutsches Institut für Entwicklungspolitik (DIE), 2000)
With the international monetary system dominated by the USA, by the European Monetary Union and Japan, all important decisions on monetary policy will continue to be taken within the G 7 framework. For the foreseeable future the IMF will have to content itself with a role that is essentially geared to ensuring the monetary stabilization of the developing and newly industrializing countries, and especially of the emerging economies. The emphasis here is on four areas of responsibility: Monetary forum: Regardless of the special role played by the G 7, the IMF should be developed into the world's main monetary forum. Only if the newly industrializing and developing countries are appropriately involved in the reform of the international financial architecture can the IMF live up to its claim to universality. In these circumstances, the establishment in the autumn of 1999 of the G 20, in which the leading industrialized and newly industrializing countries are represented, counteracts the planned upgrading of the IMF's International Monetary and Financial Committee. Economic and monetary advice for its members countries will continue to be one of the IMF's principal tasks in the future. It is the most important contribution the IMF makes to crisis prevention. The IMF should be given the mandate of an enlarged information policy, enabling it in specific cases to inform the public about critical developments in a country or even to issue a warning if it becomes clear that the government concerned is unwilling to take action against serious undesirable developments in its own country. Greater discipline over a country's economic policy might then be maintained through the markets. The financing facilities are the IMF's most important instrument in the management of financial and monetary crises. However, they form an extremely complex, bureaucratic system of arrangements, which has also lost its inner logic with the passage of time. Apart from the existing credit facilities and a new crisis facility that covers all kinds of crisis, all the facilities should be completely abandoned. The same applies to the Poverty Reduction and Growth Facility. The scope of the credit facilities should be increased accordingly, and terms of maturity should be determined flexibly to suit the nature and magnitude of the balance-of-payments problems. The IMF should expand its service functions, some of which it is already performing. They include the preparation of statistics, analyses and assessments, technical cooperation with developing countries and countries in transition and mediation, as in relations between creditors and debtor countries at the time of debt crises.
Keywords: 330